PEMBUATAN DEKSTRIN DARI TEPUNG TAPIOKA SECARA ENZIMATIK DENGAN PEMANAS MICROWAVE - Lis Pudiastuti; Tika Pratiwi; Herry Santosa (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Dextrin is partial hydrolysis product from starch with enzyme catalys. This research’s aim are to (1) make dextrin from tapioca starch, (2) learn the influence of starch concentration and liquefaction time to DE and viscosity. The process include 3 step (1) preparation, (2) formation of dextrin, and (3) result evaluated. The formation of dextrin consist of 2 phase, that is gelatinization phase which held in microwave and liquifaction phase which held in stirer tank. The control variable are starch genus (tapioca starch merck “Gunung Agung”), catalist genus (α-amylase)0,5-0,6 kg/tons dry starch, CaCl2.2H2O 40 ppm, pH 6 – 6,5, liquifaction temperature 94oC, Microwave with power 10 and defrost d2. Free variable that use are liquifaction period (30, 60, 90, 120,150,180 minutes) and starch soluion concentration (10, 15, 20, 25, 30, 35% w/v). At the end of researc, product analysed DE with volumetric method (Woodman, 1941), viscosity with Leach method (1963) and Thermo Haake method. From this reaserch, the product dextrin was maltodextrin with maximal DE 12,839. And known that (1) as long as the liquifaction time, higher DE from dextrin product and decrease in its viscocity, (2) small starch concentration produce dextrin with higher DE and smaller viscosity than high starch concentration.